The technology and science of low-speed and motorless flight : Proceedings of the second international symposium (The Soaring Society of America, 1974)
Optimun flight paths and strategies- Sailplane flight testing- Flight instruments and displays- Low reynolds -number aerodynamics- Man-powered aircraft- Ultralight glider technology- Aerodynamic design optimization - Atmospheric energy exploitation- Structural design technology- Sailplane flight testing.